Oil Extracted Moringa peregrina Seed Cake as a Feed Ingredient in Poultry: A Chemical Composition and Nutritional Value Study - Mohammed A. Al-Harthi; Youssef A. Attia; Mohamed F. Elgandy; Fulvia Bovera (Animals, 2022)
The chemical composition, antioxidant activity, tannic acid content, mineral, fatty acid, and amino acid profiles of oil-extracted Moringa peregrina seed meal (OEMPSM) were determined. Apparent (AME) and true (AMEn) metabolizable energy and apparent (AAAU) and true (TAAU) amino acid utilization were evaluated using a precision feeding trial. The protein (CP) quality was evaluated by a total efficiency analysis method. The antioxidant activity, gauged by 2,2-diphenyl-1-picrylhydrazyl (DPPH), was 237, 353, and 15.2 mg/mL for the water and ethanol extracts, and ascorbic acid, respectively. Tannic acids were 131.4 mg/100 g dry weight. The OEMPSM had 27.2% CP and 22.4, 15.1, and 15.8 MJ/kg of gross energy, AME and AMEn, respectively. The neutral detergent fiber, acid detergent fiber, and hemicellulose were 40.2, 29.7, and 10.5% DM, respectively. The 15.41% of total fatty acids were saturated and 84.57% unsaturated. The AAAU and TAAU of OEMPSM were 30.92% and 61.06%, respectively. From findings, OEMPSM comprises a valuable level of bioactive substances, amino acids, fatty acids, minerals, and energy; it can provide up to 1.12% of the requirements of total amino acids of chickens (1–21 days); however, the quality of its protein was found to be 44.6% less than that of protein of soybean meal.